Tuberculosis Arthritis: A Diagnostic Challenges - Desak Putu Gayatri Saraswati Seputra; Pande Ketut Kurniari (Indonesian Journal of Rheumatology, 2023)
Background: Tuberculosis infection still poses a significant health problem, especially in developing countries. While most of tuberculosis cases affect the pulmonary organ, this infection may also involve other organs such as bones and joints. Case presentation: We reported a case of 23-year-old female patient with a history of recurrent pain and swelling in the right knee. On physical examination of the right knee, bulging sign was found, accompanied by tenderness, warmth on palpation, and limited active and passive movement. Radiographic examination was suggestive for septic arthritis in the right knee. Debridement and biopsy were performed, and TB PCR examination of the debridement tissue was found to be positive for Mycobacterium tuberculosis. The histopathological finding was also consistent with tuberculosis infection. The patient was subsequently treated with antituberculosis drugs and underwent rehabilitation therapy, resulting in a satisfying response. Conclusion: Diagnosis of tuberculosis arthritis in this case was established based on the presence of clinical symptoms, radiological findings, tissue TB PCR, and histopathological findings. Both surgical and pharmacological interventions were performed, which yielded favorable results. Tuberculosis arthritis was often misdiagnosed as arthritis for other causes, resulting in delays in providing medical intervention. Therefore, increased understanding of tuberculosis arthritis is necessary to facilitate early diagnosis and improve therapeutic outcome.